La fabrique littéraire des territoires : quand l’Oulipo renouvelle les pratiques de l’aménagement urbain - Géraldine Molina (Territoire en Mouvement)
How does literature leave the world of books in order to fulfil itself in space and participate in changing it? Through an analysis of the collaboration of literature, architecture and urbanism, this paper aims to provide an answer to this central question. The analysis is based on literary urban planning directed by the Oulipo (Ouvroir de Littérature Potentielle) writers in collaboration with architects. How do these writers become space builders? This article, through an analysis of the effects of a literary factory stemming from urban spaces, investigates today’s dynamics of production in contemporary territories. What can we learn from these arrangements of the current processes of production of contemporary space, professional recompositions of participating actors and working approaches of the designers of space? Such an approach, exploring the links between literature, space and society, fits into the “geography of literature” perspective. Literary works are no longer merely considered from a simple textual point of view, as elaborations of more or less fictive worlds, but now are also envisaged as participants in the world building process and, in particular, in that of the modern city.